TRADISI PENYAMBUTAN DAN PENGHORMATAN TAMU DI KERATON YOGYAKARTA SEBAGAI BENTUK POLA RELASI PADA MASA PEMERINTAHAN HAMENGKU BUWANA VII DALAM NASKAH KOEPIJA DJENDRALAN - Apriyadi, Clara Shinta Anindita; Buduroh, Mamlahatun (Widyaparwa, 2023)
This research -discussed the text of Kangjeng Tuan Ingkang Wicaksana Governor General Otto van Rees (KTIWGJO), it is one of the texts in the archived manuscript of Koepija Djendralan (KD) the collection of KHP Widya Budaya Keraton Yogyakarta. The text was written in Javanese and the form of prose. This text was studied with philology analysis. Furthermore, the analysis of the content text used the theory of postcolonialism and the theory of hegemony. The purpose of this study was to present the edits and translations of the KTIWGJO text so that it was easy to read and understood by today's society and to explain the procession of welcoming and honoring guests at the Yogyakarta Palace during the reign of Sultan Hamengku Buwana VII. Analysis of the content of the KTIWGJO text, including analysis of welcome and respect upon arrival of Governor General Otto van Rees; and an analysis of the activities of Governor General Otto van Rees for seven days in Yogyakarta. The pattern of relations was analyzed using the theory of postcolonialism. Through this pattern of relations, it can add new insights into the pattern of hegemony carried out by the natives at that time and prove that not all of the colonized were backward and ignorant parties. Penelitian ini membahas teks Kangjeng Tuan Ingkang Wicaksana Gupernur Jendral Otto van Rees (KTIWGJO), salah satu teks yang berada di dalam naskah arsip Koepija Djendralan (KD) koleksi KHP Widya Budaya Keraton Yogyakarta. Teks ini tertulis dalam bahasa Jawa dan berbentuk prosa. Teks ini dikaji dengan metode filologi dan dianalisis menggunakan teori poskolonialisme serta teori hegemoni. Tujuan penelitian ini adalah untuk menyajikan suntingan dan terjemahan teks KTIWGJO agar mudah dibaca dan dipahami oleh masyarakat kini dan menjelaskan prosesi penyambutan serta penghormatan tamu di Keraton Yogyakarta pada masa pemerintahan Sultan Hamengku Buwana VII. Analisis isi terdiri dari analisis penyambutan; analisis penghormatan pada saat kedatangan Gubernur Jenderal Otto van Rees; dan analisis kegiatan Gubernur Jenderal Otto van Rees selama di Yogyakarta. Pola relasi yang dianalisis menggunakan teori poskolonialisme. Melalui pola relasi ini pula, dapat menambah wawasan baru mengenai pola hegemoni yang dilakukan oleh pihak pribumi pada masa itu dan membuktikan bahwa pihak terjajah tidak semuanya adalah pihak terbelakang dan pihak yang bodoh.